Examining attendance patterns across integrated therapies for posttraumatic stress disorder and alcohol use disorder. (January 2022) - Straus, Elizabeth; Worley, Matthew J.; Lyons, Robert; Kline, Alexander C.; Tripp, Jessica C.; Davis, Brittany C.; Haller, Moira; Angkaw, Abigail C.; Trim, Ryan S.; Norman, Sonya B.
Abstract: A substantial body of evidence supports the use of integrated treatments for posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD). Integrated trauma-focused exposure therapies reduce PTSD symptoms more than comparison treatments, including integrated coping skills therapies, but demonstrate lower attendance, raising questions regarding the relationships between attendance, outcomes, and treatment type. We aimed to examine these relationships in a RCT comparing integrated prolonged exposure ( Concurrent Treatment for PTSD and Substance Use Disorders Using Prolonged Exposure, COPE; n = 58), to integrated coping skills therapy (Seeking Safety, SS; n = 52) offered in 12 sessions, with an option to extend up to four additional sessions. Participants were categorized based on number of sessions attended (0–4; 5–8; 9–12; 13–16). Multilevel modeling revealed that only when examining therapy attendance segments individually, clinical outcomes were comparable across treatments except in the 9–12 group, with COPE resulting in greater reductions in PTSD symptoms (p < 0.001), but not in alcohol use. Extending past 12 sessions was not associated with additional clinically meaningful symptom improvement for either treatment. These results suggest that attending a complete or near complete course of exposure therapy may enhance PTSD outcomes relative to non-trauma-focused therapies. Highlights: Relationship between attendance and outcomes in integrated treatment is complicated. Exposure outperformed coping therapy for PTSD for those who completed 9–12 sessions. Extending beyond 12 sessions was not associated with further meaningful improvement.